VALIDITAS TES KETERAMPILAN BERPIKIR KREATIF MATERI TEKANAN ZAT DENGAN ANALISIS RASCH MODEL - Nurul Yuliadinda; Muslim Muslim; Ridwan Efendi (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2019)
Creative thinking skills is one of the high-level thinking skills that must be possessed by students in learning. However, to determine the students' creative thinking skills necessary measurement tools in the form of tests. Therefore, studies were conducted in order to determine the content validation and construct validation tests of creative thinking skills with Rasch analysis models. This research uses descriptive quantitative method using the design construction and validation. The construction process generates six test items that measure creative thinking skills aspects of fluency, flexibility and originality in the form of an essay. The validation process is based on the judgment of five experts and tests on 190 samples. The results of the validity of the content item has a high and very high categories.